Identification of P53 Tumor Suppressor Gene Alterations in Human Glioma Using Sscp-Pcr Technique. - Ameen, Nzar A.; Nerweyi, Farida F. A.; Sulayman, Ahmed; Jubrael, Jaladet T M. S.; Al-Rawi, Walid W. H.; Ibrahim, Sheelan H. (Science Journal of University of Zakho, 2015)
The P53 is the most commonly altered gene in cancers, which is located on chromosome 17p. Because of it is important role in the cell cycle it considered as the guardian of the genome that maintains genome integrity. In this study we analyzed DNA from 15 surgical specimens of human glioma for mutations in the p53 gene along exons 6-9 using single-strand conformation polymorphism analysis of polymerase chain reaction product (PCR-SSCP). The frequency of P53 gene mutation in gliomas examined was 26.6% (4 of 15). All 4 mutated cases were in exon 6 and no mutation was observed in exon 7,8 and 9. The results suggest the involvement of P53 gene mutation in Glioma and it might play an important role in the tumorigenesis process of patients with brain tumor in preliminary study in Duhok province.
Keywords: Brain Tumors; Glioma; SSCP-PCR; P53